Adam Małachowski i listy do niego z lat 1724-1767 w zbiorach Ossolineum - Kobierecki, Michał (Acta Universitatis Lodziensis. Folia Historica, 2000)
Mr Adam Małachowski (about 1706-1767) is a characteristic representative of Saxonic period. He was an active member of Seym, advocate of liberum veto and wanted to preserve the rights and privileges of noblemen. Also, he was often elected to Seym, tribunals and deputations. Although he did not succeed in getting a senatorial seat, he was a remarkable figure in Parliament thanks to his relations with political parties and nobility in many provinces. Letters of many persons who wrote to him in different matters have been preserved to the present day. Most of the correspondence concerned political problems including the one with Mr Jan Klemens Branicki – the great royal hetman, Mr Jerzy Mniszech – the great royal major domo, Mr Tomasz Sołtyk – the voivode in Łęczyca and Mr Kajetan Sołtyk - the bishop in Kijów. These letters reflect Mr Malachowski’s connections with the political parties of Mr Branicki and Mr Mniszech as well as the mechanisms of mutual influence of magnate and a nobleman. A different type of correspondence are the letters from Mr A. Antoszewski, Mr Gordon – the superintendent of the Royal Treasury or Mr Wojciech Piastuszyński – the steward of an estate in Chwałowice. The main subject of these letters are the problem related to economy with political and regional information fairly often accompanying them. Political and family subjects are also to be found in the letters of Peter and Stanislaus Małachowscy - Adam’s sons. Besides abundant correspondence there are single letters or two and three written by one author. The main themes here are the requests for a candidate’s support to an office, different cases tried in tribunals or the requests for the future remembrance. Thanks to studies on Mr Adam Malachowski’s correspondence, we have far more information about the person himself as well as the role he played in the community of noblemen. We can assume that he was a close and valuable ally for magnates. For many people in the community of noblemen he was the man who could help somebody in getting promotion, he could give support for a given case tried in tribunals or just do another favour.